Analysis Of Maternal Risk Factor On Stunting In Children In Palembang City - Pariyana; Iche Andriyani Liberty; Muhammad Aziz; Mariana; Machlery.AP; Kevin.S (International Journal of Science, Technology & Management, 2021)
The incidence of stunting is one of the sustainable development goals target. To achieve it, an intervention that is right and significant and in accordance with the priority of stunting risk factors. The priority of risk factors is influenced by many things in different places. Thus, this research is the key as a strategy in identifying priority factors as a prevention strategy against stunting toddlers in Palembang. This research is an analytical observational research with case control approach. The samples were collected using purposive sampling techniques and 170 research subjects were obtained. The data was collected from Health Centre of Palembang City by measuring the height according to the age of the toddlers and carried out interviews with the toddler’s mother. There results were analysed using Chi-square statistical tests. The analysis results obtained which had a meaningful relation with stunting incidence are maternal age, maternal work, maternal body height, maternal body weight, history of anemia during pregnancy, number of birth, pregnancy gap factor, history of iron or folate supplement consumption history, number of ANC visits, history of infectious diseases during pregnancy, and exclusive breastfeeding. The most dominant risk factors in sequence the chances of stunting children are the number of children more than one by 12 times, anemia during pregnancy by 9 times, mothers who have a high risk age has 7 times, the mother's height is not ideal by 6 times, the distance of pregnancy is equal to or less than 24 months by 4 times, an ANC visit is less than 4 times the chance of 4 times , do not give exclusive breast milk by 4 times, mothers who work outside the house by 3 times, do not consume iron or folate supplements by 3 times.